The Japanese Clinical Practice Guidelines for Management of Sepsis and Septic Shock 2016 (J‐SSCG 2016). Issue 1 (5th February 2018) - Nishida, Osamu; Ogura, Hiroshi; Egi, Moritoki; Fujishima, Seitaro; Hayashi, Yoshiro; Iba, Toshiaki; Imaizumi, Hitoshi; Inoue, Shigeaki; Kakihana, Yasuyuki; Kotani, Joji; Kushimoto, Shigeki; Masuda, Yoshiki; et al.
Abstract : Background and Purpose: The Japanese Clinical Practice Guidelines for Management of Sepsis and Septic Shock 2016 (J‐SSCG 2016), a Japanese‐specific set of clinical practice guidelines for sepsis and septic shock created jointly by the Japanese Society of Intensive Care Medicine and the Japanese Association for Acute Medicine, was first released in February 2017 in Japanese. An English‐language version of these guidelines was created based on the contents of the original Japanese‐language version. Methods: Members of the Japanese Society of Intensive Care Medicine and the Japanese Association for Acute Medicine were selected and organized into 19 committee members and 52 working group members. The guidelines were prepared in accordance with the Medical Information Network Distribution Service (Minds) creation procedures. The Academic Guidelines Promotion Team was organized to oversee and provide academic support to the respective activities allocated to each Guideline Creation Team. To improve quality assurance and workflow transparency, a mutual peer review system was established, and discussions within each team were open to the public. Public comments were collected once after the initial formulation of a clinical question (CQ), and twice during the review of the final draft. Recommendations were determined to have been adopted after obtaining support from a two‐thirds (>66.6%) majority vote of each of the 19 committee members. Results: A total of 87 CQs were selected among 19 clinical areas, including pediatric topics and several other important areas not covered in the first edition of the Japanese guidelines (J‐SSCG 2012). The approval rate obtained through committee voting, in addition to ratings of the strengths of the recommendation and its supporting evidence were also added to each recommendation statement. We conducted meta‐analyses for 29 CQs. Thirty seven CQs contained recommendations in the form of an expert consensus due to insufficient evidence. No recommendations were provided for 5 CQs. Conclusions: Based on the evidence gathered, we were able to formulate Japanese‐specific clinical practice guidelines that are tailored to the Japanese context in a highly transparent manner. These guidelines can easily be used not only by specialists, but also by non‐specialists, general clinicians, nurses, pharmacists, clinical engineers, and other healthcare professionals.